2017
DOI: 10.3892/mmr.2017.7629
|View full text |Cite
|
Sign up to set email alerts
|

Chondromodulin-I suppresses tumorigenesis of human osteosarcoma cells

Abstract: Osteosarcoma is the most common type of bone cancer, and accounts for ~3% of cancers that occurring in children. Chondromodulin‑I (ChM-I) is a 25 kDa glycoprotein that is expressed mainly in cartilage. ChM-I demonstrates anti‑angiogenic activity and has been suggested to inhibit endothelial cells from invading cartilage, and then has been shown to be an inhibitor of tumorigenesis. However, it remains unclear if ChM‑I has any direct anti‑tumorigenesis role on osteosarcoma. Therefore, the present study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The role of Chm-1 in cancers is largely unknown. The anti-angiogenic properties of Chm-1 are postulated to inhibit tumour growth, propagation, and metastasis, indicating that loss of Chm-1 function may induce tumorigenesis [42]. Significantly, Chm-1 appears to be implicated in the pathogenesis of the two most common childhood bone tumours, osteosarcoma and Ewing’s sarcoma (ES) [42, 43].…”
Section: The Role Of Chm-1 In Cancer and Heart Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…The role of Chm-1 in cancers is largely unknown. The anti-angiogenic properties of Chm-1 are postulated to inhibit tumour growth, propagation, and metastasis, indicating that loss of Chm-1 function may induce tumorigenesis [42]. Significantly, Chm-1 appears to be implicated in the pathogenesis of the two most common childhood bone tumours, osteosarcoma and Ewing’s sarcoma (ES) [42, 43].…”
Section: The Role Of Chm-1 In Cancer and Heart Diseasementioning
confidence: 99%
“…The anti-angiogenic properties of Chm-1 are postulated to inhibit tumour growth, propagation, and metastasis, indicating that loss of Chm-1 function may induce tumorigenesis [42]. Significantly, Chm-1 appears to be implicated in the pathogenesis of the two most common childhood bone tumours, osteosarcoma and Ewing’s sarcoma (ES) [42, 43]. Chm-1 has been shown to inhibit the growth and proliferation of human osteosarcoma cells in vivo, and to inhibit the invasion and migration of human osteosarcoma cells in vitro [42].…”
Section: The Role Of Chm-1 In Cancer and Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…PPI analysis found that LECT2 has the strongest correlation with LECT1, SVIL, FGG, and DDX46. The study of LECT1 on osteosarcoma cells in vivo showed that it inhibited their growth and proliferation (Lin et al, 2017). Knockdown of DDX46 inhibited osteosarcoma cell proliferation and tumor growth in vivo (Jiang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%